Cohesion of the European regional space - Proniewski, Marek (IGiPZ PAN, 2016)
The purpose of the EU cohesion policy is to reduce disparities at the level of economic, social and spatial development of the underdeveloped regions. The Europe 2020 Strategy establishesmore growth- and innovation-oriented investments. The main objective of this paper is to analyze and evaluate the differences and dynamics of the EU regions at the NUTS 2 level, characterized by the selected variables in the economic, social and territorial accessibility (transport infrastructure) area to determine the clusters of different levels of disparities in the EU regions (HDI) and transport infrastructure as well as to examine their interdependence. Calculations were based on statistical data acquired from Eurostat databases. The results confirm a distinctively clear inequality of economic development in the European regional space between Central and Eastern Europe as well as Northern and Western Europe regions, with the highest growth of dynamics identified in the regions of the countries that joined the EU in 2007 and 2004. The analysis also identifies the European regions with a high level of spatial cohesion (accessibility) and validates the thesis about the presence of interdependence between the EU regional development and spatial cohesion (accessibility) of the regions.
Każdy numer posiada własny tytuł.
Keywords: Unia Europejska; spójność gospodarcza; spójność społeczna; spójność przestrzenna; rozwój regionalny; HDI; infrastruktura transportowa